2013
DOI: 10.5380/ce.v18i2.32587
|View full text |Cite
|
Sign up to set email alerts
|

O Uso Da Acupressão Para Evolução Do Trabalho De Parto E Alívio Da Dor

Abstract: RESUMO:Esta revisão integrativa teve o objetivo de buscar as evidências disponíveis na literatura que abordassem o uso da acupressão durante a evolução do trabalho de parto e alívio da dor. Realizou-se uma pesquisa nas bases de dados Scopus, Medline, Cinahal e SciELO, viabilizando a inclusão de 10 estudos, publicados entre 2002 e 2012, que aplicaram a acupressão nos pontos Sanyinyiao, Hegu e Zhiyin durante a fase ativa do trabalho de parto. Os resultados demonstraram que a técnica em análise aparenta diminuir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
1
7
0
2
Order By: Relevance
“…Most studies (75%) included in an integrative review conducted by Mafetoni et al 17 in which they applied TENS for pain relief during labor demonstrated increased pain reduction responses compared with the placebo group, corroborating the findings of the present study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most studies (75%) included in an integrative review conducted by Mafetoni et al 17 in which they applied TENS for pain relief during labor demonstrated increased pain reduction responses compared with the placebo group, corroborating the findings of the present study.…”
Section: Discussionsupporting
confidence: 88%
“…There is also weakness in relation to blinding clinical trials, where only the studies of Santana et al, 14 Báez-Suárez et al, 2 and Njogu et al 16 performed some kind of blinding, which compromises the power of evidence in these studies. 2 14 16 17 18 19 …”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, it is understood to be necessary for the professional to use non-invasive strategies to promote and recover the pregnant woman's well-being. In this sense, acupressure has been used by nurses on pregnant women, providing physical and emotional well-being during the birth process (11) .…”
Section: ] (Pregnant Woman 03)mentioning
confidence: 99%
“…Just like the use of dates, acupressure, at point SP6, was also related to a shorter period of active phase ( 13 ) . In general, CIHP are less invasive and generally lower-cost methods, which can help when there is a need to induce or augment the labor.…”
Section: Introductionmentioning
confidence: 99%